2012
DOI: 10.1111/j.1095-9270.2012.00344.x
|View full text |Cite
|
Sign up to set email alerts
|

A Late Bronze Age Shipwreck with a Metal Cargo from Hishuley Carmel, Israel

Abstract: A 13th‐century‐BC shipwreck site, Hishuley Carmel, is described and discussed. It provides direct evidence for marine transport of copper and tin along the Israeli coast and may indicate inland and maritime trade‐routes of metals in the Mediterranean. The shipwreck represents a supply‐system providing the demand for bronze in the Levant. Trace‐elements and lead‐isotope analysis suggest that the copper came from Cyprus, similarly to bun and oxhide ingots from Uluburun. The source of the tin cannot yet be ascert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 31 publications
(47 reference statements)
1
13
1
Order By: Relevance
“…to Apliki copper was sufficient to pull it away from the Apliki LI range. Lead contents for Eastern Desert cassiterite have never been measured, but typical lead contents for contemporary tin ingots are in the 10-100 µg/g range (Galili et al, 2013). Exceptions exist, however, with 600-1200 µg/g Pb measured in some ingots (Begemann et al, 1999;Molofsky et al, 2014).…”
Section: Some Of the Other Intermediate Samples Could Be Identified Amentioning
confidence: 99%
“…to Apliki copper was sufficient to pull it away from the Apliki LI range. Lead contents for Eastern Desert cassiterite have never been measured, but typical lead contents for contemporary tin ingots are in the 10-100 µg/g range (Galili et al, 2013). Exceptions exist, however, with 600-1200 µg/g Pb measured in some ingots (Begemann et al, 1999;Molofsky et al, 2014).…”
Section: Some Of the Other Intermediate Samples Could Be Identified Amentioning
confidence: 99%
“…The latter also applies to a group of 15 tin ingots recovered in four campaigns from an alleged shipwreck at the coast of Hishuley Carmel, Israel (Figs 1 and 4A), together with two oxhide copper ingots and several stone anchors [23–27]. Because the archaeological context was missing, the exact dating of the finds is uncertain, but ‘Cypro-Minoan’ symbols inscribed on the surface of several ingots suggest a LBA date of around 1300 BCE [23–24; 26]. For the same reason, Maddin et al [21] and Stech-Wheeler et al [28] assigned two rectangular tin ingots found off the Israeli coast near Haifa to the LBA (Fig 4B, 8251 and 8252).…”
Section: Introductionmentioning
confidence: 99%
“…(b) Three out of 30 tin ingots from Haifa with Cypro-Minoan inscriptions with their original label from the literature. Scale applies to all ingots on the figure (photos: E. Galili, Fig 4A modified and reprinted from [26] under a CC BY license, with permission from the International Journal of Nautical Archaeology, original copyright 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The possibility that the site represents jettison rather than a wrecked ship is worth discussing. A similar nearby site containing heavy, metal artefacts concentrated on the sea bottom within the surf zone, has been discussed in detail previously (Galili and Rosen, : 17–18). It was concluded that during stormy sea conditions in this region, any act of jettisoning should have occurred in deeper water, further off shore and away from the coastal breakers zone, and the same is true for the Megadim site.…”
Section: Discussionmentioning
confidence: 76%
“…Over the millennia, storms along this coast have driven many ships ashore, where they were grounded and disintegrated in the breaker zone (Galili et al ., : 366). Analysis of scores of sites along the Israeli coast showed that only heavy objects remained at wreck‐sites in the open, unprotected surf zone (Galili et al ., 2002, : 17–18, Galili and Rosen : 123).…”
Section: Discussionmentioning
confidence: 99%